2002
DOI: 10.1097/00003677-200201000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Motor Control Strategies Revealed in the Structure of Motor Variability

Abstract: We describe an uncontrolled manifold hypothesis, which suggests a particular solution for the notorious problem of motor redundancy. A body of recent experiments supports the uncontrolled manifold hypothesis and shows its ability to discover biological strategies of the coordination of apparently redundant motor systems. The hypothesis and associated computational apparatus have great potential for application in the areas of motor rehabilitation and motor skill acquisiton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
495
2
12

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 676 publications
(533 citation statements)
references
References 7 publications
24
495
2
12
Order By: Relevance
“…Although we can provide no direct evidence from this report that different points within a UCM correspond to different values of directional stiffness, this seems to be a reasonable assumption given endpoint stiffness estimates reported in earlier studies (Shadmehr et al 1993). The result is consistent with our view that variance in the values of movement components is not simply a reflection of noise (Latash et al 2002b;Scholz and Schöner 1999). …”
Section: Goal-equivalent Joint Configuration Variance Increased In Resupporting
confidence: 92%
See 1 more Smart Citation
“…Although we can provide no direct evidence from this report that different points within a UCM correspond to different values of directional stiffness, this seems to be a reasonable assumption given endpoint stiffness estimates reported in earlier studies (Shadmehr et al 1993). The result is consistent with our view that variance in the values of movement components is not simply a reflection of noise (Latash et al 2002b;Scholz and Schöner 1999). …”
Section: Goal-equivalent Joint Configuration Variance Increased In Resupporting
confidence: 92%
“…This principle emphasizes error compensation, or more generally, flexible solutions to the coordination of the motor elements underlying a motor task. Such flexibility may be the most important feature of a functional synergy (Latash et al 2002b). …”
Section: Introductionmentioning
confidence: 99%
“…In the four-finger MVC pressing tasks it was found that the variance of the total maximal force output was smaller than the sum of variances of the maximal individual finger forces (Li et al 1998a(Li et al , 1998b. The reduction of the force variance at the multi-finger level suggested the existence of an inter-compensation among individual digits also confirmed in a series of further studies (Latash et al 2001(Latash et al , 2002a(Latash et al , 2002b. Santello and Soechting (2000) examined the control of five-digit grasping by measuring gripping forces when subjects lifted and held a handle.…”
Section: Multi-finger Synergies Stabilizing Force Directionmentioning
confidence: 87%
“…The existence of synergies in multi-finger force production is well documented and revealed in both pressing and grasping tasks (Li et al 1998a(Li et al , 1998bLatash et al 2001Latash et al , 2002aLatash et al , 2002b. In the four-finger MVC pressing tasks it was found that the variance of the total maximal force output was smaller than the sum of variances of the maximal individual finger forces (Li et al 1998a(Li et al , 1998b.…”
Section: Multi-finger Synergies Stabilizing Force Directionmentioning
confidence: 96%
See 1 more Smart Citation